Arachidonic acid and docosahexaenoic acid as predictors of retinopathy of prematurityseverity: a narrative review - Garcia Pacotaype, Luisa Lanue (2026)
This systematic review and meta-analysis aimed to evaluate the association between plasma levels of arachidonic acid(ARA) and docosahexaenoic acid (DHA) and the severity of retinopathy of prematurity (ROP), a major cause of blindnessin premature infants. A comprehensive search was conducted across multiple databases, including PubMed, Scopus,Embase, and Google Scholar, identifying five cohort studies with robust methodological quality. These studies includedbetween 58 and 207 premature infants, most of whom were born at less than 28 weeks of gestational age. Although someindividual findings suggested that higher levels of ARA or DHA might have a protective effect, the results of the meta-analysisdid not demonstrate a statistically significant association between these fatty acids and the development or severity ofROP. The pooled odds ratio (OR) was 0.96 for ARA and 0.71 for DHA, with no significant heterogeneity among the studies.In conclusion, current evidence does not support the hypothesis that plasma levels of ARA and DHA predict the severityof ROP. Further research with larger sample sizes and more homogeneous methodologies is required to provide morerobust evidence.